2009
DOI: 10.2308/accr.2009.84.4.1209
|View full text |Cite
|
Sign up to set email alerts
|

Fraud Brainstorming Using Computer-Mediated Communication: The Effects of Brainstorming Technique and Facilitation

Abstract: This study experimentally investigates the effectiveness of computer-mediated brainstorming in the context of the SAS No. 99 mandated fraud brainstorming requirement. Results indicate that brainstorming effectiveness is significantly higher for teams brainstorming electronically relative to teams using traditional face-to-face brainstorming. There is no significant difference in brainstorming effectiveness between electronic interactive brainstorming and electronic nominal brainstorming. Brainstorming effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 46 publications
2
36
0
3
Order By: Relevance
“…Interestingly, Gallupe et al (1991) found no significant difference between interactive and nominal electronic brainstorming. Lynch, Murthy, & Engle (2009) also found no significant difference between the interactive and nominal group brainstorming techniques, in the context of a fraud brainstorming task. On the other hand, Valacich et al (1994) found that larger groups brainstorming in interactive mode using technology produced a significantly higher number of ideas compared to electronic nominal groups.…”
Section: Brainstorming Techniquesmentioning
confidence: 80%
“…Interestingly, Gallupe et al (1991) found no significant difference between interactive and nominal electronic brainstorming. Lynch, Murthy, & Engle (2009) also found no significant difference between the interactive and nominal group brainstorming techniques, in the context of a fraud brainstorming task. On the other hand, Valacich et al (1994) found that larger groups brainstorming in interactive mode using technology produced a significantly higher number of ideas compared to electronic nominal groups.…”
Section: Brainstorming Techniquesmentioning
confidence: 80%
“…It consists of papers related to the procedures used by audit rms in the accomplishment of their services. We can point out audit team brainstorming, analytical procedures, quality of paperwork, assessment face-toface of paperwork, electronic evaluation of paperwork, work plan, and digital analysis (Bhattacharjee, Moreno, & Riley, 2012;Lynch, Murthy, & Engle, 2009;Trompeter & Wright, 2010). is theme had a decrease of 24% on its representativeness (5.3%) and it was published every year of the study, just in 10-21 journals.…”
Section: Declining Themesmentioning
confidence: 99%
“…SAS 99 requires auditors identify specific fraud risks and SAS 109 requires auditors identify additional causes of potential material misstatement in the financial statement during brainstorming (Landis, 2008;Hammersley et al, 2010;Carpenter, 2007;Hoffman and Zimbelman, 2009;Bellovary and Johnstone, 2007;Hunton and Gold, 2010;Lynch et al, 2009). The participating team may include the whole audit team, including audit partner, audit manager, senior and new staff, and the time spent on the session varies from 15 mins to 2 hours, mainly 30 mins to 1 hour (Bellovary and Johnstone, 2007).…”
Section: Background On Audit Brainstorming Sessionsmentioning
confidence: 99%